Chalcone derived benzoheterodiazepines for medicinal applications: A Two-pot and one-pot synthetic approach - Saba, Farooq; Zainab, Ngaini (Wiley Periodicals, 2021)
The production of effective drugs has continuously been a challenging process for researchers due to the occurrence of resistive diseases. Drugs derived from natural product-based compounds as an active scaffold have gained interest in drug development due to a wide range of biological properties. Benzoheterodiazepines, a natural product derivative of bicyclic chalcones have been widely reported with various therapeutic potentials. This review discusses current synthetic methods in the preparation of benzoheterodiazepine derivatives (i.e., homocyclic benzoheterodiazepine, heterocyclic benzoheterodiazepine, bisbenzoheterodiazepine, and fused benzoheterodiazepine) via two-pot and one-pot synthetic routes. Several reaction protocols following both synthetic routes have been developed for efficient and higher yields that offer access to different functionalization of benzoheterodiazepines are comprehensively described. This review is important in the heterocyclic chemistry of benzoheterodiazepines and pharmacological industries in drug development processes